2022
DOI: 10.3354/meps14157
|View full text |Cite
|
Sign up to set email alerts
|

Timing mussel deployments to improve reintroduction success and restoration efficiency

Abstract: The loss of newly translocated species directly contributes to low rates of reintroduction success in both terrestrial and aquatic ecosystems. In this study, experimental reintroductions of green-lipped mussels Perna canaliculus into a shallow coastal habitat were conducted across 5 week-long experimental translocations within a 10 mo period (April 2021-January 2022) to relate temporal variations in predator abundance, predator size, and environmental parameters (water temperature, rainfall, days before/after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…However, when left unprotected at certain sites they can quickly be removed by local predators (e.g., by predatory sea stars in their historic range, Wilcox et al, 2018;Benjamin et al, 2023). One-two weeks were considered sufficient to compare the potential impacts of predators and environmental factors on mussel survival to inform site selection criteria as previous work has indicated that predators will remove newly translocated mussels within the first few days following placement on the seafloor (Alder et al, 2020(Alder et al, , 2022.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when left unprotected at certain sites they can quickly be removed by local predators (e.g., by predatory sea stars in their historic range, Wilcox et al, 2018;Benjamin et al, 2023). One-two weeks were considered sufficient to compare the potential impacts of predators and environmental factors on mussel survival to inform site selection criteria as previous work has indicated that predators will remove newly translocated mussels within the first few days following placement on the seafloor (Alder et al, 2020(Alder et al, , 2022.…”
Section: Methodsmentioning
confidence: 99%
“…• Turbidity (Percent of turbidity-obscured images): Since predator species like Tamure/Australasian snapper (Hereafter Australasian snapper) are visual hunters and suspended sediment can impact mussel filtration rates, the number of turbidity-obscured images recorded for each deployment were included as a proxy for water column turbidity. Previous work has also indicated a positive relationship between the number of turbid images recorded and the number of predators observed, which negatively interact with mussel survival (Alder et al, 2022). All images with < 0.5 m of visibility (i.e., where adjacent mussel groups were not clearly visible) were categorised as turbidityobscured images.…”
Section: Site Classification and Environmental Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely due to the availability of Bivalvia in the benthic habitat at this specific site, as snapper sampled from Rat Island only included 0.15% Bivalvia in their gut contents. Green-lipped mussels have been rarely reported in the gut contents of snapper sampled from natural habitats (Third, 2022;Usmar, 2012), but snapper are known to predate on them when they are available (Alder et al, 2021(Alder et al, , 2022a(Alder et al, , 2022b. Blue mussels have never been recorded in previous snapper diets in New Zealand (Colman, 1972;Drummond, 2020;Godfriaux, 1970;Russell, 1983;Third, 2022;Usmar, 2012).…”
Section: Comparison To Broader Hauraki Gulf Snapper Populationmentioning
confidence: 99%